2015
DOI: 10.1002/ieam.1634
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the fit of biotic ligand model validation data in a risk management decision context

Abstract: Biotic ligand models (BLMs) have advanced the ability to predict the concentrations of metals in surface waters likely to harm aquatic organisms. BLMs have been developed for several metals including Cu, Zn, Cd, and Ag. Additionally, the US Environmental Protection Agency has published guidance on the use of a BLM to develop water quality criteria for Cu. To validate the predictive performance of many BLMs, model predictions based on test water quality have been compared with corresponding laboratory toxicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Verschoor et al (2011) used the BLM to assess the temporal-and geographical-dependent risk characterization rations that were derived by dividing site-specific adverse effect level (ECx or LCx). The BLM-based WQC has been widely used for the risk management decision context in several countries, such as US, European Union, and UK (WFD-UKTAG, 2014; Lathouri and Korre, 2015;McLaughlin, 2015;Rüdel et al, 2015). However, the protectiveness of current WQC based on metal bioavailability for metal toxicity to aquatic organism is still unclear in Taiwan.…”
Section: Water Quality Criteria Regulation and Risk Managementmentioning
confidence: 98%
See 2 more Smart Citations
“…Verschoor et al (2011) used the BLM to assess the temporal-and geographical-dependent risk characterization rations that were derived by dividing site-specific adverse effect level (ECx or LCx). The BLM-based WQC has been widely used for the risk management decision context in several countries, such as US, European Union, and UK (WFD-UKTAG, 2014; Lathouri and Korre, 2015;McLaughlin, 2015;Rüdel et al, 2015). However, the protectiveness of current WQC based on metal bioavailability for metal toxicity to aquatic organism is still unclear in Taiwan.…”
Section: Water Quality Criteria Regulation and Risk Managementmentioning
confidence: 98%
“…As expected, high cation contents of Agongdian and Love Rivers heavily decreased Zn bioavailability in the higher WER conditions. Recent studies indicated that the site-specific bioavailabilitybased approach is considered to be the best one to account for the environmental quality standard and risk management of regional and local water chemistry characteristics in regulatory organizations (Lathouri and Korre, 2015;McLaughlin, 2015;Rüdel et al, 2015). Verschoor et al (2011) used the BLM to assess the temporal-and geographical-dependent risk characterization rations that were derived by dividing site-specific adverse effect level (ECx or LCx).…”
Section: Water Quality Criteria Regulation and Risk Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…The capability of BLM to differentiate locations in terms of risks was reviewed by many authors (e.g. DeSchamphelaere et al, 2005; Van Sprang et al, 2009; McLauglin, 2015).…”
Section: Water Composition and Toxicitymentioning
confidence: 99%
“…In recognition of the abovementioned limitations, BLMs are validated using synthetic and natural waters prior to being considered acceptable for broader use, with their acceptability being assessed by determining the proportion of predictions (based on test water chemistry) that fall within a factor of 2 of the actual observed toxicity (McLaughlin ). The literature suggests that a BLM is considered acceptable if more than 90% of the predictions fall within a factor of 2 of the observed toxicity (Bury et al ; Niyogi and Wood ; Peters, Lofts et al ; Nys et al ).…”
Section: Strengths Limitations and Potential Applications Of Water mentioning
confidence: 99%